Optimalisasi Perencanaan Administratif dalam Administrasi Pendidikan untuk Peningkatan Mutu Layanan Pendidikan di Indonesia - Dianis Svari, Ni Made Fanny (Jayapangus Press, 2023)
The National Education System Law (UU Sisdiknas) serves as a crucial foundation for directing education in Indonesia, emphasizing the development of capabilities, character formation, and national civilization. In the context of the learning organization, high-quality and professional educational administration, especially school administrative staff, plays a vital role in ensuring the efficiency and effectiveness of the educational process. The focus of this research is on evaluating the quality of educational administration and developing strategies to enhance the quality of administrative services in schools. The research methodology employed is qualitative descriptive with a literature review approach. The findings indicate that educational management and administrative staff play a crucial role in managing and improving the quality of education. Management functions, such as planning, organizing, implementing, and supervising, adopt the PDCA cycle model to effectively achieve educational goals. Educational administrative staff, in functions such as planning, organizing, moving, supervising, employee arrangement, directing, coordinating, reporting, and funding, are instrumental in organizing administrative activities in educational institutions. The educational management process, encompassing planning, organizing, directing, coordinating, financing, monitoring, and evaluation, forms a cycle to ensure the achievement of goals and the improvement of educational quality. Development strategies for administrative staff, through organizational, task, and personnel analysis, as well as the implementation of training and development, play a key role in enhancing the quality and skills of educational administrative staff. Training and development, plays a key role in improving the quality and skills of education administration personnel. The development of educational administrative personnel brings significant benefits, including better decision-making abilities, improved skills, increased competitiveness in the work environment, and strengthening work culture. Quality management of administrative services in the educational environment involves the stages of identification, determination of inputs and outputs, determination of criteria and methods, identification of employees, development of work culture, implementation of training, and evaluation. Educational institutions can ensure that administrative staff have the necessary competencies to manage administrative tasks efficiently.